2022
DOI: 10.1002/slct.202200442
|View full text |Cite
|
Sign up to set email alerts
|

3D‐QSAR, Molecular Docking and Molecular Dynamics Analysis of 1,2,3,4‐Tetrahydroquinoxalines as BRD4/BD2 Inhibitors

Abstract: BRD4 plays an indispensable role in cell cycle regulation, affecting processes such as cell proliferation, apoptosis and transcription. In this article, a three-dimensional quantitative conformational relationship (3D-QSAR) was used to investigate the molecular simulations related to 45 tetrahydrooxazole BRD4/BD2 selective inhibitors. 3D-QSAR models were developed based on two different analytical methods, COMFA and COMSIA. All CoMSIA field combinations were compared together and the best CoMSIA model was sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…It has been observed that the A 5 complex has a lower RMSD than other complexes, representing its more excellent stability. The RMSF of the protein reveals the stability of protein per residue throughout the simulation [23] . RMSF analyses of PDK2 backbone residues were calculated to examine the fluctuation and flexibility of amino acid residues pending equilibrium simulation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been observed that the A 5 complex has a lower RMSD than other complexes, representing its more excellent stability. The RMSF of the protein reveals the stability of protein per residue throughout the simulation [23] . RMSF analyses of PDK2 backbone residues were calculated to examine the fluctuation and flexibility of amino acid residues pending equilibrium simulation.…”
Section: Resultsmentioning
confidence: 99%
“…of protein per residue throughout the simulation. [23] RMSF analyses of PDK2 backbone residues were calculated to examine the fluctuation and flexibility of amino acid residues pending equilibrium simulation. Based on the obtained results, RMSF value of more than 0.43 nm was not observed for any amino acid residues (Figure 4B).…”
Section: Chemistryselectmentioning
confidence: 99%
“…[10] we have developed novel compounds against αtubulin receptors using several tools of computational chemistry: 3D-QSAR (CoMFA and CoMSIA), Molecular Docking, Molecular Dynamics simulation, and ADMET prediction technique. CoMFA and CoMSIA models have been successfully performed and validated by the PLS method [11] to discover more powerful compounds. [10] The binding analysis is an interesting technique that corroborates the potency of compound activity by studying the ligand-receptor interactions [12] and is confirmed by Re-docking technique on the original ligand (Guanosine-5'-Triphosphate).…”
Section: Introductionmentioning
confidence: 99%